Alveolar mimics with periodic strain and its effect on the cell layer formation. Issue 9 (27th June 2020) - Radiom, Milad; He, Yong; Peng‐Wang, Juan; Baeza‐Squiban, Armelle; Berret, Jean‐François; Chen, Yong
Abstract: We report on the development of a new model of alveolar air–tissue interface on a chip. The model consists of an array of suspended hexagonal monolayers of gelatin nanofibers supported by microframes and a microfluidic device for the patch integration. The suspended monolayers are deformed to a central displacement of 40–80 µm at the air–liquid interface by application of air pressure in the range of 200–1, 000 Pa. With respect to the diameter of the monolayers, that is, 500 µm, this displacement corresponds to a linear strain of 2–10% in agreement with the physiological strain range in the lung alveoli. The culture of A549 cells on the monolayers for an incubation time of 1–3 days showed viability in the model. We exerted a periodic strain of 5% at a frequency of 0.2 Hz for 1 hr to the cells. We found that the cells were strongly coupled to the nanofibers, but the strain reduced the coupling and induced remodeling of the actin cytoskeleton, which led to a better tissue formation. Our model can serve as a versatile tool in lung investigations such as in inhalation toxicology and therapy. Abstract : An alveolar air–tissue interface‐on‐a‐chip is developed using an array of suspended monolayers of gelatin nanofibers on honeycomb microframes. The gelatin nanofibers at air–liquid interface are modulated via application of air pressure in a microfluidic chip to apply in vivo like linear strains to alveolar cell line culture. Mechanical strain is found to lead to morphological change in cells and formation of uniform cell layer on gelatin nanofibers, while no loss of viability is observed with the cells.